USING VIRTUAL FIELD TRIP TO IMPROVE STUDENTS' WRITING SKILLS - Elsani Istianah Kaelani, - (2021)
Writing has been considered as challenging language skill to learn. This study investigates using virtual field trips to improve students' writing skills, focusing on writing recount text. This study used collaborative classroom action research involving eleventh students of class nine junior high school in Purwakarta, West Java, Indonesia was carried out in two cycles with data collection of series of writing tests, observation, and interviews. The result indicated there was an improvement after using virtual field trips in students' writing. Virtual field trips tended to improve students ' writing skills through a series of activities, watching virtual field trip videos, taking notes, getting feedback from peers and teachers, and doing worksheets in every meeting. Virtual field trips can help students to develop their ideas in their writing. As a result, students could write long paragraphs with supporting details. By noting the information, students found during the virtual field trip, and they could organize their ideas according to the generic structure of the recount text. By watching the video trip and hearing information from the tour guides, the students knew the vocabulary they wanted to use. In addition, it confirmed that most students responded positively to the use of virtual field trips. This research recommends that teachers use virtual field trips and improve students' writing skills, making learning more interactive and enjoyable.